Nuclear Reactor Kinetics электронный курс - Лавриненко, С. В. специалист в области теплоэнергетики старший преподаватель Томского политехнического университета 1986- (TPU Moodle, 2019)
Each topic includes a presentation and a book with the necessary theoretical material. The information contained in the books will be necessary to perform and protect individual homework, laboratory work, tests and examinations. In the course posted Task. After completing the task, you need to issue a report and load it into the course. Print a report is not necessary. Each task must be protected in class. The course contains guidelines for laboratory work. Laboratory work is done in class, and reports are drawn up at home. Lab reports must also be uploaded to the course. Print a report is not necessary. Every laboratory work must be protected. In the course of the course, it is necessary to write two test papers at a conference week. If you complete and successfully defend all the elements of the course, you will be allowed to take the exam. Upon successful completion of all course elements and their protection, an automatic mark for the exam on the amount of points gained during the semester can be entered.